2004
DOI: 10.1111/j.1600-0714.2004.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the c‐erbB‐2 receptor protein in glandular salivary secretions

Abstract: These results suggest that the protein, c-erbB-2, is present in relatively equal amounts in both SP and SS glandular secretions. Elevated glandular salivary c-erbB-2 concentrations could be useful as a preliminary, non-invasive test in clinical decision making when diagnosing salivary gland carcinomas. Additionally, this marker may have utility in distinguishing between oral lesions that are benign, pre-malignant and malignant in the oral cavity. Further research is required to determine if these findings have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Determining the levels of erbB2 protein is a reliable method for early diagnosis and screening of cancer (Streckfus et al, 2004). Bayrak et al (2013) found that overexpression of genes is seen in many solid tumors, which is useful in disease prognosis and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the levels of erbB2 protein is a reliable method for early diagnosis and screening of cancer (Streckfus et al, 2004). Bayrak et al (2013) found that overexpression of genes is seen in many solid tumors, which is useful in disease prognosis and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the level of erbB2 protein is a reliable method for the initial diagnosis and screening of cancers (Streckfus et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that RNAs are actively secreted. These RNAs could originate from secreting cells or they could be produced elsewhere in the body, travel through the circulatory system, and be secreted into the saliva (3,17,18 ). It has been reported that a breast cancer marker protein, c-erb-B-2, also known as HER-2/neu, is found in stratified saliva fractions (17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like many microand macromolecules, RNA in salivary gland secretions could originate from acinar cells or by circulation (1,3,17,18 ). GCF is also a likely source of RNA, because many blood cells and their cellular components are released into the oral cavity from GCF (19 ).…”
mentioning
confidence: 99%
“…Saliva proteins may have diagnostic value for human oral and systemic diseases. For instance, the soluble fragments of the c-erbB-2 oncogene and CA 15-3 were found significantly up-regulated in the saliva samples of breast cancer patients than in those of healthy controls and patients with benign tumors [385,386]. Elevated levels of salivary CEA, defensin-1, TNF-alpha, IL-1, 6 and 8, and CD44 were detected in patients of oral cancer [387][388][389][390][391][392][393].…”
Section: Application To Human Disease Detectionmentioning
confidence: 99%